2006
DOI: 10.1128/jvi.01362-06
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Analysis of Infectious Virus-Like Particles of Uukuniemi Virus ( Bunyaviridae ): a Useful System for Studying Bunyaviral Packaging and Budding

Abstract: In the present report we describe an infectious virus-like particle (VLP) system for the Uukuniemi (UUK) virus, a member of the Bunyaviridae family. It utilizes our recently developed reverse genetic system based on the RNA polymerase I minigenome system for UUK virus used to study replication, encapsidation, and transcription by monitoring reporter gene expression. Here, we have added the glycoprotein precursor expression plasmid together with the minigenome, nucleoprotein, and polymerase to generate VLPs, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
80
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 57 publications
(78 reference statements)
10
80
2
Order By: Relevance
“…These conformational changes have been reported to occur at pH 6.4 in the G C of La Crosse virus (15) and between pH 6.0 and 6.2 in the G C of UUKV (36). We have recently observed a conformational change of UUKV glycoprotein capsomers in virions at pH 6.0, studied using electron cryo-tomography (31). To study if pH-dependent conformational changes would also occur in RVFV, we analyzed samples prepared at pH 6.0, in addition to those prepared at pH 7.4 (see Materials and Methods).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These conformational changes have been reported to occur at pH 6.4 in the G C of La Crosse virus (15) and between pH 6.0 and 6.2 in the G C of UUKV (36). We have recently observed a conformational change of UUKV glycoprotein capsomers in virions at pH 6.0, studied using electron cryo-tomography (31). To study if pH-dependent conformational changes would also occur in RVFV, we analyzed samples prepared at pH 6.0, in addition to those prepared at pH 7.4 (see Materials and Methods).…”
Section: Discussionmentioning
confidence: 60%
“…Although similar ordering was observed for UUKV, the RNPs seem to be less important for particle assembly in UUKV than in RVFV. UUKV glycoproteins are sufficient to form empty virus-like particles without the nucleocapsid protein (31). In the case of RVFV, glycoproteins alone are not sufficient for generating virus-like particles, but nucleocapsid protein, and potentially also RNA, are required (16).…”
Section: Discussionmentioning
confidence: 99%
“…ift Valley fever virus (RVFV) (the genus Phlebovirus, family Bunyaviridae) carries three single-stranded, negative-sense RNA segments, L, M, and S. The viral RNA-dependent RNA polymerase (L protein), envelope Gn/Gc glycoproteins, and N protein, all of which are essential for virus replication, are encoded in L, M, and S RNAs, respectively; hence, copackaging of the three genomic RNA segments into a virus particle is necessary for the generation of infectious RVFV, yet our understanding of bunyavirus RNA packaging mechanisms is still in its infancy (2,4,11,15,19,23,26). Using RVFV, we address several unexplored questions in bunyavirus genome packaging, including the biological activities of the noncoding regions (NCRs) of each viral RNA segment for RNA packaging, the identification of RNA packaging signals, and a possible role(s) of the coding regions in viral RNA packaging.…”
mentioning
confidence: 99%
“…Previous work on Uukuniemi phlebovirus (38,39) and BUNV orthobunyavirus (42) indicated that the cytoplasmic tails of the viral glycoproteins, particularly that of Gn, were indispensable for viral replication. This was confirmed by Piper et al (40), who showed that the cytoplasmic tail of RVFV Gn recruits the L protein, nucleocapsid protein, and the genomic RNA into virions.…”
Section: Discussionmentioning
confidence: 99%
“…We show here that a recombinant RVFV can maintain a viral-like segment expressing a foreign gene without any selective pressure or apparent advantage to the virus. This system thus provides a valuable tool to facilitate the further exploration of genomic segment packaging in the context of a fully functional virus, rather than VLP assays as have been previously used (14,20,38). It also provides the potential for RVFV to act as a vector for other foreign gene sequences.…”
Section: Discussionmentioning
confidence: 99%